Taguchi optimization of geopolymer concrete produced with rice husk ash and ceramic dust - Memiş, Selçuk; Bılal, Mohamed Ahmed Mohamed (Springer Science and Business Media LLC, 2021)
Metakaolin, fly ash, and mostly granulated blast furnace slag (GBFS) are traditionally used in the production of geopolymer. This study, adding to the knowledge base on geopolymer concretes as an alternative to cement mixtures, explored an experimental approach that investigates the use of ceramic dust (CD) and rice husk ash (RHA) with high SiO content instead of GBFS in the production of geopolymers. For this purpose, instead of GBFS, RHA at proportions of 0, 5%, 10%, and 15% and CD at proportions of 0, 10%, 20%, and 30% were used in the production of geopolymer concrete. In addition, groups were determined with a Taguchi L16 matrix with NaOH (an important material in geopolymer production) at 12, 14, 16, and 18 molality. Varying combinations of flow diameter, density, porosity, and water absorption rate were used, and their performance under high temperatures in terms of compressive strength was evaluated. The use of RHA in geopolymer concretes produced using CD and RHA had a negative effect on the flow and water absorption rates. However, the use of CD had a positive effect, and geopolymer concretes with high density and porosity were obtained. In addition, it was determined that strengths > 70 MPa could only be obtained if 5-20% CD were used at 14-16 molality. The resistance of geopolymer concretes to high temperatures is lower than normal concretes. However, when comparing RHA and CD, it was determined that the use of CD would be more effective on geopolymer materials, and special measures should be taken at temperatures > 450 °C.
Keywords: Ceramics; Construction Materials; Dust; Oryza; Coal Ash; 12. Responsible consumption